PEMBINAAN KOMPETENSI GURU DALAM PEMBELAJARAN - Betha Oktariya (UNIVERSITAS BENGKULU, 2019)
This study improved the competence of teachers in the implementation of learning at Elementary School 11 South Bengkulu. Classroom action researchwas used as the method in reseacrh, and the data was collected by interview, observation, and documentation. The result showed that of the study indicate there is very high increase in teacher competence and competence.